Teacher education and development in active learning methods - Medeiros, Rodolfo De Oliveira [UNESP]; Marin, Maria José Sanches; Lazarini, Carlos Alberto; De Castro, Rosane Michelli [UNESP]; Higa, Elza De Fátima Ribeiro (FapUNIFESP (SciELO), 2022)
Active learning methods have shown themselves to be important tools in the teaching and learning process, making the continuous education of university teachers in the area of health necessary. The aim of this study was to analyze education in this area and the strategies suggested for the continuous professional development of teachers. We conducted a qualitative field study grounded in the premises of social representation theory with 40 teachers from a higher education institution. The results pointed to two core thematic categories (continuous education and permanent education) and four subcategories (training workshops, digital information and communication technologies, reflecting on practice, and training workshops). The findings of this study can contribute to strengthening strategies for the continuous professional development of university teachers in the area of health.
Formación docente en metodologías de aprendizaje activo
Formação docente em metodologias de aprendizagem ativa
Keywords: Continuous education; Health; Human resource training in health; Problem-based learning; Teachers